EVALUATION SUBJECTIVE EXPERIENCES IN THE PHYSICAL ACTIVITY, DEPRESSION AND SELF-PERCEPTION OF THE DAILY LIFE ACTIVITIES IN AGED PRACTITIONERS OF RESISTENCE TRAINING (Fiep Bulletin - online, 2015)
The aging process causes functional and mannering alterations that affect the human beings in characteristic ways. Following this line of thought, the decline of the physical capacity is one of the many problems faced for the aged ones that it contributes for a depression of the mood state, as well as reduction of the effectiveness in the AVDs. The objective of this study was to evaluate subjective experiences in the physical activity, depression and auto-perception of the AVDs in aged practitioners of resistence training. The population was represented by aged active, physically practicing ones of resistence training.The sample was composed for 17 aged ones, being 7 of masculine sex and 10 of the feminine sex, with age varying enters the 60 82 years, with average age of 69 years. The used instruments had been 3 questionnaires: Scale of evaluation of subjective experiences in the physical activity (Mc Auley and Courneya 1994); Scale to evaluate the depression (Fiatarone 1996) and Scale of auto-perception the performance of AVDs (Andreotti and Okuma 1999), all protocolled by Matsudo (2005). The analysis statistics was of the descriptive type. The results on subjective experiences, in the three studied aspects - positive, negative affection and fatigue - you prop up are favorable. How much to depression 17% it has trend for depression and 83% had not presented trend. In relation the auto-perception of the AVDs, 82.4% has "very good" functional capacity and 17.6% have "good" functional capacity. Analyzing the gotten data, it can be inferred that in its majority, the citizens had presented favorable conditions in the subjective experiences, "very good" functional capacity and had disclosed not to have trend for the depression. It is still standed out that had presented you prop up favorable in the subjective experiences had been the ones that had still presented depressive indications and "good" functional capacity.
Keywords: physical activity; aging; depression; self-perception; subjective experiences